An “Aquarelle” Pelike from A.E. Liutsenko’s Excavations of the Pantikapaion Necropolis: the Problems of Date, Attributing and Semantic - Mogilevskaya, Ekaterina V. (Actual Problems of Theory and History of Art, 2013)
The present study considers an Hermitage piece of Hellenistic pottery from the group known as Bosporian “aquarelle” pelikai once made in the North Pontic region. This vessel with added color painting showing a half-figure of a syncretic goddess should be referred to as belonging to a local type of sepulchral pottery imitating Attic red-figure vases of the Kerch style. The author of the article discusses semantics of the painted image, which seems to be thoroughly familiar, on the one hand, from general religious tradition of the Classical world, and on the other — from that of Asia Minor in particular. The study also touches upon the technique of vase painting and the date of the group of vessels under consideration, based on its exact archaeological context.
Keywords: Hellenistic pottery; Bosporian “aquarelle” pelikai; Pantikapaion Necropolis